A case of Krukenberg tumor, eight years after treatment of gastric cancer - Karagul, Servet; Sumer, Fatih; Onur, Asim; Tardu, Ali; Dagli, Adile Ferda; Kayaalp, Cuneyt (Marmara Univ, Fac Medicine, 2018)
Krukenberg tumor is a rare metastatic tumor of the ovary. The primary tumors are usually gastrointestinal cancers. Most of the Krukenberg tumors reported in the literature occurred within the first 2 years after treatment of the primary disease. Herein, we present a case of Krukenberg tumor in a 37-year-old woman who previously underwent surgery and chemotherapy for stomach cancer. This patient is noteworthy because it is one of the few documented cases of ovarian metastasis appearing after a disease-free period of 8 years following treatment of the primary tumor. Krukenberg tumors are associated with poor prognosis; therefore, regular gynecological examination in female patients with history of gastric cancer is very important for the early diagnosis and treatment of this disease.
Mide kanseri tedavisinden 8 yil sonra Gelişen Krukenberg tümörü olgusu
Keywords: Krukenberg tumor; Gastric cancer; Ovarian metastasis